2023
DOI: 10.1108/cg-06-2022-0261
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and bank performance: evidence from banking sector of Pakistan

Abstract: Purpose The aim of this study is to understand how board structure, size of audit committee (AC), gender diversity and ownership structure influence banks’ performance in Pakistan. This study also aims to examine how various dimensions of governance differently affect the different measures of bank performance. Design/methodology/approach This study used panel estimation techniques to quantify the impact of various elements of corporate governance on bank performance by taking annual data of 19 Pakistani ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…These findings support the agency theory which recommends that a larger managerial ownership stake will induce managers to make better decisions that lead to better firm performance. This significant and positive relationship align with the findings of Annisa et al (2021), Huynh et al (2020), Faisal (2015, Bhagat and Bolton (2013), Onakoya et al (2013), Tomar and Bino (2012), Fooladi and Ghodratollah (2011), Cornett et al (2009), Krivogorsky (2006), Gedajlovic and Shapiro (2002), Demsetz and Villalonga (2001), R. K. Morck et al (2000), Hart (1995), Mehran (1995), Jensen (1993) who reported positive and significant influence of board ownership on financial performance. Also in tandem with the findings of Alshouha et al (2021), Tayachi et al (2021), Alabdullah (2018), Shleifer and Vishny (1997), Vu et al (2018), Nyaguthii et al (2019), Bhagat and Bolton (2013), Z.…”
Section: Discussion Of Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These findings support the agency theory which recommends that a larger managerial ownership stake will induce managers to make better decisions that lead to better firm performance. This significant and positive relationship align with the findings of Annisa et al (2021), Huynh et al (2020), Faisal (2015, Bhagat and Bolton (2013), Onakoya et al (2013), Tomar and Bino (2012), Fooladi and Ghodratollah (2011), Cornett et al (2009), Krivogorsky (2006), Gedajlovic and Shapiro (2002), Demsetz and Villalonga (2001), R. K. Morck et al (2000), Hart (1995), Mehran (1995), Jensen (1993) who reported positive and significant influence of board ownership on financial performance. Also in tandem with the findings of Alshouha et al (2021), Tayachi et al (2021), Alabdullah (2018), Shleifer and Vishny (1997), Vu et al (2018), Nyaguthii et al (2019), Bhagat and Bolton (2013), Z.…”
Section: Discussion Of Resultssupporting
confidence: 83%
“…A number of empirical studies have dwelt on this topic, ownership structure and firm performance. On a general note, Annisa et al (2021), Tomar and Bino (2012), Krivogorsky (2006), Gedajlovic and Shapiro (2002) found a substantial influence of ownership structure on bank performance. Onakoya et al (2013) found positive impact of ownership structure on ROE of nine banks in Nigeria (2006Nigeria ( -2010.…”
Section: Review Of Empirical Literaturementioning
confidence: 91%
“…Banking sector is quite relevant to the variables examined in this study because the banks have a well-established manager-subordinate system where the subordinates continuously receive both the career and psychosocial mentoring. Pakistan has a very competitive and fast growing banking sector (Athar, Chughtai & Rashid, 2023), where the bank branches are characterized by modern organizational systems that are run by highly qualified and well trained people (Sumbal, Ključnikov, Durst, Ferraris & Saeed, 2023).…”
Section: Respondents and Settingsmentioning
confidence: 99%
“…It is considered that institutional theory is established as a dynamic component that includes factors that influence the interaction between different actors (Athar et al 2023). It is possible to observe that the relationship between organizational innovation, organi-zational learning, the sustainability innovation performance, and the board directors is based on the behavior that firms assume, the government structure, and the strategies that ensure success in the long-term context in which they operate (Melis and Nawaz 2023;Jouber 2023).…”
Section: Adaptation To the Institutional Environment And Organization...mentioning
confidence: 99%
“…Therefore, the institutional theory provides the lenses from which it is possible to understand how organizations and their board directors respond to the pressures and regulations of the context that regulate the search for innovation and sustainability (Naveed et al 2023). In this way, institutional pressures and organizational innovation vary with the stakeholders' expectations (Athar et al 2023). The board of directors acts by the institutional norms and the expectations related to the culture of innovation within the firm.…”
Section: Adaptation To the Institutional Environment And Organization...mentioning
confidence: 99%